PENGEMBANGAN MEDIA PAPAN METAMORFOSIS SEMPURNA TEMATIK KELAS 4 MADRASAH IBTIDAIYAH - Muhammad Ulin Nuha; Ma’as Shobirin; Ummu Jauharin Farda (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
This study aims to determine the development of the thematic perfect metamorphosis board media for grade 4 at MI Miftahul Falah Mindahan Batealit Jepara. This research uses the development method (research and development). This research method uses the development model of Sugiono's ten steps. Due to time constraints, the researcher developed up to five steps: potential and problems, data collection, product design, design validation, and design revision. Data collection techniques in this study used interviews, observation, questionnaires, and documentation. The results of the needs analysis sheet by the fourth grade teacher of MI Miftahul Falah and it can be concluded that the science map learning media board on metamorphosis material is really needed. Based on the validation results, it can be concluded that the product developed is in the